From a tick in external auditory canal to pediatric Lyme disease - A. Buonamico; J. Silvestri; M. Ciuffreda; E. Pisello; G. Castellana; S. Sorrenti; L. Brugiaferri; C. Sacchetti; F. Lacchè; C. Chinigioli; V. Biscaccianti; A. Pennacchi; et al. (Pediatric Anesthesia and Critical Care Journal, 2023)
Lyme disease is an infectious disease caused by Borrelia Burgdorferi infection. It is a zoonosis transmitted by ticks and is common in Europe. Its clinical presentation in- cludes an early manifestation, which can cause local and systemic symptoms, and a late form. Erythema migrans, arthritis, facial palsy, meningitis and carditis are possible complications of the disease. We report a case of a 4-year child who presented with fever and upper and lower limbs maculopapular cutaneous rash. Left otoscopy showed the presence of a black, round-shaped foreign body attached to the postero-superior aspect of the exter- nal auditory canal (EAC), which was identified as a tick. Prompt removal of the tick was proposed. Considering the age of the patient, general anesthesia was indicated. After orotracheal intubation, the lesion was completely removed under microscopic vision. Subsequently, intra- venous antibiotic therapy was continued; the day after, the patient was transferred to a pediatric department where attentive monitoring and therapy were continued, with complete resolution of the symptoms.